Cuerpo femenino y abyección en los desnudos de Débora Arango - Aguilar Rubiano, Beira; Mahecha Bustos, Iván (CUADERNOS KÓRE, 2012)
Female Body and Abjection in the nude paintings of Debora Arango. The representation of the female body in the nude paintings of Debora Arango was perceived as a transgression of the traditional canons of representation of women. This transgression shared with the analysis of abjection, the fact of being seen considered as disruptive of social and moral norms which were those prevailing in the colombian conservative government in the early twentieth century. This led to stereotype the work of Debora Arango and to her exclusion and self-isolation from the artistic community.